A study on the maximum gained output ratio of single-effect solar humidification-dehumidification desalination. (15th November 2017) - Wu, Gang; Kutlu, Cagri; Zheng, Hongfei; Su, Yuehong; Cui, Dandan
Highlights: The model presented here predicts the minimum work requirement of HDH desalination system. An ideal single-effect CAOW water-heated HDH system is 100.21 kJ for producing 1 kg freshwater. The GOR of system increases with the increase in the operating temperature from 293 K to 370 K. The maximum GOR for a solar HDH desalination system is generally fewer than 12.5. Abstract: Based on the minimum work requirement for the humidification- dehumidification (HDH) desalination processes, the potential maximum gained output ratio (GOR) of a single-effect closed-air open-water (CAOW) water-heated solar humidification-dehumidification desalination system is calculated in this paper. The theoretical results show that the minimum work requirement for an ideal HDH desalination system increases with the operating temperature. Moreover, when concentration ratio of used solar concentrators changes, maximum GOR has slightly change. Higher than 340 K, the maximum GOR will evidently increase with the operating temperature. When the concentration ratio of used solar concentrators increases, the maximum GOR rises. The calculation results also indicate that the maximum GOR for a solar HDH desalination system is generally fewer than 12.5 (370 K) according to different concentration ratios. Mass concentration of sodium chloride has slightly effect on maximum GOR. The effect on evaporation work is too small to compare with dehumidification work. Having set the top limit of HDH desalination system performance will ensure to see the potential of increase of these system's performance.